Frequency of Hypomagnesaemia in Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Muhammad Younus, Fareena Farooq, Sohail Anwar, Yasir Nasir (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease of the airways and lungs which occurs secondary to exposure to tobacco, biomass fuel smoke and harmful gases. Every time patient develops acute exacerbations of COPD lung functions further declines compromising quality of life. Magnesium is an important element involved in many functions of respiratory tract by releasing neurohumoral mediators, mucociliary clearance, stabilization of mast cells and bronchodilation of respiratory tract smooth muscles. Objective: The objective of this study is to find frequency of hypomagnesaemia in acute exacerbation of chronic obstructive pulmonary disease. Material and Method: This Cross sectional study was conducted at Institute of chest Medicine, Mayo hospital Lahore. A total of 135 cases fulfilling inclusion criteria were enrolled in study. Informed written consent was taken from patients or attendant and then their demographic data (including name, age, gender, address and duration of disease) was also recorded. All patients with COPD exacerbation were assessed for their magnesium levels. A blood sample of 5 cc was drawn in aseptic measures with help of staff nurse. The blood sample was sent to same hospital laboratory and their magnesium level was recorded and hypomagnesaemia was labeled according to operational definition. Results: Mean age of patients was 47.11 ± 10.92 years. Males were 125(92.59%) and 10(7.41%) were female. There were 33(24.44%) case who had mild, 31(22.96%) cases had moderate, 35(25.93%) cases had severe and 36(26.67%) cases had very severe disease. According to operational definition, 54(40%) cases had hypomagnesemia and 81(60%) cases had normal magnesium levels. Conclusion: Hypomagnesemia was found in 40% patients of acute exacerbation of chronic obstructive pulmonary disease. Hence, in future magnesium supplementation can be added along with standard treatment to improve the outcome. By correcting magnesium levels, we can further reduce the severity of disease and prevent the related complications. Keywords: Chronic obstructive pulmonary disease, hypomagnesaemia, Magnesium level, Acute Exacerbation